(3RHOI GdWHs - (3CHh EHQGgje , ESeGYjd Hf GdMSf GdMSjfj GdLQLGfj,J (B531 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg aCYde Ce eHfi GdWH heOGQ CeQg Ydi eYQaI MGdJi HOf GdEfSGf ef GdUMI hGdeQV s
(3BNQgG (B:s
(3hEPG JCcdJ GddPYI YhdL HGdOhGA GdMGQ , hJWdi fhGMjgG HGdWjf GdCQefi hGdNd WdGA ,hYhdL HYdGL GdbQhM s
(3Cdag HWQjbI LOGhd eaUdI Objbg eWhdIs
(3eUOQI HagQS JaUjdi dCHhGH GdcJGH hehVhYGJg s
(3cJHJ ddWHjH GdTjN eUWai Hf GdTjN YHO GdYRjR GdTgjQ HGdGNdGUs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs